Answer:
34107cm
Step-by-step explanation:
No, A and B are not independent events
Step-by-step explanation:
Let us study the meaning independent probability
- Two events are independent if the result of the second event is not affected by the result of the first event
- If A and B are independent events, the probability of both events is the product of the probabilities of the both events P (A and B) = P(A) · P(B)
∵ P(A) = ![\frac{3}{14}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B14%7D)
∵ P(B) = ![\frac{1}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B5%7D)
∴ P(A) . P(B) =
× ![\frac{1}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B5%7D)
∴ P(A) . P(B) = ![\frac{3(1)}{14(5)}](https://tex.z-dn.net/?f=%5Cfrac%7B3%281%29%7D%7B14%285%29%7D)
∴ P(A) . P(B) = ![\frac{3}{70}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B70%7D)
∵ P(A and B) = ![\frac{3}{65}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B65%7D)
∵ P(A) . P(B) = ![\frac{3}{70}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B70%7D)
- The two answers are not equal
∴ P (A and B) ≠ P(A) · P(B)
- In independent events P (A and B) = P(A) · P(B)
∴ A and B are not independent events
No, A and B are not independent events
Learn more:
You can learn more about probability in brainly.com/question/13053309
#LearnwithBrainly
Answer:
153, 9
Step-by-step explanation:
multiply and 7 and 9
Answer:
![(x^\frac{3}{8})^\frac{3}{4} = \sqrt[32]{x^9}](https://tex.z-dn.net/?f=%28x%5E%5Cfrac%7B3%7D%7B8%7D%29%5E%5Cfrac%7B3%7D%7B4%7D%20%20%3D%20%5Csqrt%5B32%5D%7Bx%5E9%7D)
Step-by-step explanation:
Given
![(x^\frac{3}{8})^\frac{3}{4}](https://tex.z-dn.net/?f=%28x%5E%5Cfrac%7B3%7D%7B8%7D%29%5E%5Cfrac%7B3%7D%7B4%7D)
Required
Convert to radical form
![(x^\frac{3}{8})^\frac{3}{4}](https://tex.z-dn.net/?f=%28x%5E%5Cfrac%7B3%7D%7B8%7D%29%5E%5Cfrac%7B3%7D%7B4%7D)
Evaluate the exponents
![(x^\frac{3}{8})^\frac{3}{4} = x^\frac{3*3}{8*4}](https://tex.z-dn.net/?f=%28x%5E%5Cfrac%7B3%7D%7B8%7D%29%5E%5Cfrac%7B3%7D%7B4%7D%20%3D%20x%5E%5Cfrac%7B3%2A3%7D%7B8%2A4%7D)
![(x^\frac{3}{8})^\frac{3}{4} = x^\frac{9}{32}](https://tex.z-dn.net/?f=%28x%5E%5Cfrac%7B3%7D%7B8%7D%29%5E%5Cfrac%7B3%7D%7B4%7D%20%3D%20x%5E%5Cfrac%7B9%7D%7B32%7D)
Split the exponent
![(x^\frac{3}{8})^\frac{3}{4} = (x^9)^\frac{1}{32}](https://tex.z-dn.net/?f=%28x%5E%5Cfrac%7B3%7D%7B8%7D%29%5E%5Cfrac%7B3%7D%7B4%7D%20%3D%20%28x%5E9%29%5E%5Cfrac%7B1%7D%7B32%7D)
Apply the following law of indices
![(x^a)^\frac{1}{b} = \sqrt[b]{x^a}](https://tex.z-dn.net/?f=%28x%5Ea%29%5E%5Cfrac%7B1%7D%7Bb%7D%20%3D%20%5Csqrt%5Bb%5D%7Bx%5Ea%7D)
So, we have:
![(x^\frac{3}{8})^\frac{3}{4} = \sqrt[32]{x^9}](https://tex.z-dn.net/?f=%28x%5E%5Cfrac%7B3%7D%7B8%7D%29%5E%5Cfrac%7B3%7D%7B4%7D%20%20%3D%20%5Csqrt%5B32%5D%7Bx%5E9%7D)